Sovereign Debt Portfolios, Bond Risks, and the Credibility of Monetary Policy - DU, WENXIN; PFLUEGER, CAROLIN E.; SCHREGER, JESSE (Journal of Finance, 2020)
ABSTRACT We document that governments whose local currency debt provides them with greater hedging benefits actually borrow more in foreign currency. We introduce two features into a government's debt portfolio choice problem to explain this finding: risk‐averse lenders and lack of monetary policy commitment. A government without commitment chooses excessively countercyclical inflation ex post, which leads risk‐averse lenders to require a risk premium ex ante. This makes local currency debt too expensive from the government's perspective and thereby discourages the government from borrowing in its own currency.